2023
DOI: 10.3389/fonc.2023.1070505
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic classification of non-small cell lung cancer patient-derived xenografts by a digital pathology approach: A pilot study

Abstract: IntroductionGenetically characterized patient-derived tumor xenografts (PDX) are a valuable resource to understand the biological complexity of cancer and to investigate new therapeutic approaches. Previous studies, however, lack information about metabolic features of PDXs, which may limit testing of metabolism targeting drugs.MethodsIn this pilot study, we investigated by immunohistochemistry (IHC) expression of five essential metabolism-associated markers in a set of lung adenocarcinoma PDX samples previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Human NSCLC tumors have enhanced glucose oxidation 4 , 62 , but the mechanisms remain to be addressed. We found that in NSCLC cells CIP2A knockdown significantly increased the glycolysis rate and lactate production and inhibited OXPHOS, whereas CIP2A overexpression suppressed glycolysis and increased OXPHOS.…”
Section: Discussionmentioning
confidence: 99%
“…Human NSCLC tumors have enhanced glucose oxidation 4 , 62 , but the mechanisms remain to be addressed. We found that in NSCLC cells CIP2A knockdown significantly increased the glycolysis rate and lactate production and inhibited OXPHOS, whereas CIP2A overexpression suppressed glycolysis and increased OXPHOS.…”
Section: Discussionmentioning
confidence: 99%